Investigating the Impact of Leadership Styles on Finance and Accounting Specialists’ Performance - Adesuyi, Isaac Olufemi; Oludoyi, Isaac Olakunle; Bamise, Funke; Ajani, Abiola Joshua (Buhalterinės apskaitos teorija ir praktika, 2025)
This study examined the impact of leadership styles (transformational, transactional, and democratic) on finance and accounting specialists’ productivity and commitment in selected deposit money banks in Akure, Ondo State, Nigeria. The study employed a cross-sectional survey approach. Data was collected from 179 employees through structured questionnaires. The findings revealed that transactional and transformational leadership styles significantly enhance employee productivity; democratic leadership did not show a significant impact on productivity. In terms of employee commitment, transactional and transformational leadership were again found to be significant predictors, while democratic leadership showed no significant effect. The study concludes that transactional and transformational leadership styles are essential for enhancing employee productivity and commitment in the banking sector. It recommends that deposit money banks focus on developing these leadership capabilities through targeted training programs. This study contributes to the existing literature by providing empirical evidence on the effectiveness of different leadership styles on finance and accounting specialists’ performance. This offers insights for both scholars and practitioners in the field of organizational leadership.